Interleukin‐10 reduces scar formation in both animal and human cutaneous wounds: Results of two preclinical and phase II randomized control studies. Issue 3 (29th April 2013) - Kieran, Ingrid; Knock, Amanda; Bush, James; So, Karen; Metcalfe, Anthony; Hobson, Rosalind; Mason, Tracey; O'Kane, Sharon; Ferguson, Mark
Abstract Cutaneous scarring affects up to 100 million people per annum. There is no effective scar reducing/preventing therapeutic developed to date. Interleukin (IL)‐10 is an anti‐inflammatory and antifibrotic cytokine. In the embryo it is important for scarless wound repair. We investigated the effect on wound healing and scarring of a double deletion of the IL‐10 and IL‐4 genes in a knockout (KO) mouse model, and also the effect of exogenous addition of recombinant human (rh) IL‐10 into rat and human cutaneous incisions. Mouse study: Two incisions were made on the dorsal skin of 20 double IL‐4/IL‐10 KO mice and 20 wild‐type (WT) controls. Rat study: Three concentrations of rhIL‐10 were investigated. Four incisions were made on the dorsal skin of 30 rats. Each rat received two concentrations. Each incision receiving a concentration of rhIL‐10 was matched with a control incision, which received either placebo or standard care. Human study: Eight concentrations of rhIL‐10 were investigated. Four incisions were made on each arm of 175 healthy volunteers. Four incisions received four different concentrations, which were matched with four control incisions that received either standard care or placebo. KO mice healed with poor scar histology and increased inflammation. rhIL‐10–treated rat incisions healed with decreased inflammation, better scar histology, and better macroscopic scar appearance. rhIL‐10–treated human incisions at low concentrations healed with better macroscopic scar appearance and less red scars. IL‐10 is an important cytokine in wound healing and its suppression of inflammation and scarring is demonstrated in mice and rats with a translational effect in humans.